Mending Fences : The Evolution of Moscow's China Policy from Brezhnev to Yeltsin - Wishnick, Elizabeth (Book collections on Project MUSE., 2014)
Examining Russian-Chinese relations from Moscow's perspective, this important study illuminates the forces driving Moscow's China policy from 1969 to the 1990s, and concludes that the future of the partnership depends on forces of change.